Patients’ expectation and satisfaction with complete denture before and after the therapy - Zou, Yun; Zhan, Desong (Vojnosanitetski pregled, 2015)
Background/Aim. Difficulties in the acceptance of dentures are multifactorial including psychosocial ones. It is questionable whether the patients’ satisfaction depends only on the complete denture therapy characteristics. The aim of the study was to evaluated patients’ expectation and satisfaction with complete dentures before and after the treatment concerning phonetics, chewing, comfort of use and aesthetics. Methods. Forty complete edentulous patients rated their expectation before and satisfaction after the treatment based on a questionnaire scores. Patient-related variables regarding age, gender and previous experience (whether worn complete denture or not) were also recorded. Results. Patients’ rating for expectations were higher than the satisfaction after treatment regarding phonetics, chewing, comfort of use and aesthetics. A negative significant correlation was shown between the items before and after the treatment rating for phonetics, chewing, comfort of use and aesthetics. No statistical correlation was found between all the evaluated aspects’ (i.e. phonetics, chewing, comfort of use and aesthetics) of expectation and satisfaction, and age, gender, and previous experience except a weak negative correlation noticed between age and comfort of denture use. Conclusion. Patients’ expectations ratings significantly exceeded their satisfactions. Expectations and satisfaction ratings were irrespective of gender and patients previous experience.